2022
DOI: 10.1002/adhm.202201038
|View full text |Cite
|
Sign up to set email alerts
|

A Cancer Cell Membrane‐Derived Biomimetic Nanocarrier for Synergistic Photothermal/Gene Therapy by Efficient Delivery of CRISPR/Cas9 and Gold Nanorods

Abstract: Bimodal synergistic therapy produces superadditive effect for enhanced therapeutic efficacy. However, how to efficiently and simultaneously deliver several kinds of therapeutic agents is still challenging. A cancer cell membrane‐derived nanocarrier (mCas9‐sGNRs) is proposed for synergistic photothermal/gene therapy (PTT/GT) by efficient delivery of clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated protein 9 (Cas9) and gold nanorods (GNRs). In this approach, Cas9 proteins can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…90 (F) Schematic illustration of the synthesis procedures of mCas9-sGNRs and the processes of combined PTT/gene therapy. 93 For example, liposomes were fused with exosomes to form hybrid exosomes, and successful encapsulation of dCas9-sgRNA expression vectors can double the delivery efficiency (Fig. 4C).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…90 (F) Schematic illustration of the synthesis procedures of mCas9-sGNRs and the processes of combined PTT/gene therapy. 93 For example, liposomes were fused with exosomes to form hybrid exosomes, and successful encapsulation of dCas9-sgRNA expression vectors can double the delivery efficiency (Fig. 4C).…”
Section: Reviewmentioning
confidence: 99%
“…4F). 93 The CRISPR-Cas9 gene editing system for disease therapy is a very new approach and recent studies have reported their application in nanotechnology-based delivery and disease therapy using extracellular vesicles and vesicles derived from cell membranes. We believe that the development of nanoplatforms based on gene editing technology using cell association has promising applications in the field of delivery systems and disease treatment.…”
Section: Cell Delivery Strategies and Their Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a low level of ATP restrained the expression of P-gp (Figure 3K), an efficient drug efflux transporter, to increase the sensitivity of MCF-7 Adr cells to DOX. In addition, ATP reduction also decreased the expression of heat shock protein 70 (HSP70) (Figure 3K), a stress response protein which defends against hyperthermia, [30] to enhance the efficiency of PTT. Unsurprisingly, our CS/NPs greatly promoted apoptosis ratios in both parental and drug-resistant MCF-7 cells compared with free DOX, A780, DOX+A780, and NPs (Figure 3L,M and Figure S4G,H, Supporting Information).…”
Section: The Mechanisms Of Cs/nps Surmount Cancer Chemo-phototherapy ...mentioning
confidence: 99%
“…[27][28][29][30] Among them, gold nanorods have been widely used in promising drug delivery thanks to their large specific surface area and facile synthesis method. [31][32][33][34][35][36] Moreover, due to their tunable surface plasmon and photothermal effects, gold nanorods are extensively famous for generating hyperthermia (>50 °C) for tumor photothermal therapy (PTT) under a near-infrared (NIR) laser. [31,34,[36][37] Interestingly, recent research has been reported that a few photothermal agents including black phosphorus, AuPd alloy nanoparticles, and carbon nanotubes could produce mild localized heat (40-43 °C) for osteogenesis and mineralization.…”
Section: Introductionmentioning
confidence: 99%